(untitled) (The Journal of Psychology and Sociology, 2017)
This article discusses the features of the treatment of convicted persons on the basis of psychology and pedagogical methods. In this direction substantial assistance have organized today in the penal system, psychological services, providing assistance not only in psychodiagnostics convicted, but also in the recommendations on the use of various methods of exposure (both on individual personality, and the group of convicts). Special attention is paid to basic correction of convicts. The main means of correction of convicts is to obtain primary, basic secondary, general secondary, technical and vocational education. The detailed analysis is given to educational programs. Educational programs based on the content and direction (destination) are divided into: – general education (typical, work); – professional (typical, work); – additional. General educational programs are aimed at the solution of problems of formation of the general culture of the person, the person to adapt to life in society, to provide a basis for informed choice and development of the profession, specialty. Thus, comprehensive training programs are designed not only to studying a certain amount of knowledge, but also to their education and development, so they are most closely suited to perform the basic tasks of corrections – corrections prisoners. Key words: Penal Execution Code of the Republic of Kazakhstan, Law of the Republic of Kazakhstan “On Education”, personality, correction of convicts, influence of correction, articles of correction, comprehensive training programs, psychological service, pedagogical collective, regime.